Let p ( x ) be a monic quartic polynomial such that p ( 1 ) = 6 , p ( − 2 ) = 3 , p ( 3 ) = − 2 and p ( − 4 ) = − 9 . Find ∣ p ( 4 ) + 4 ∣ .
This problem is a part of this set .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let p ( x ) = x 4 + a x 3 + b x 2 + c x + d , then:
p ( 1 ) p ( − 2 ) p ( 3 ) p ( − 4 ) = = = = 1 + a + b + c + d 1 6 − 8 a + 4 b − 2 c + d 8 1 + 2 7 a + 9 b + 3 c + d 2 5 6 − 6 4 a + 1 6 b − 4 c + d = = = = 6 3 − 2 − 9
This implies that: ⎣ ⎢ ⎢ ⎡ 1 − 8 8 1 2 5 6 1 4 2 7 − 6 4 1 − 2 3 − 4 1 1 1 1 ⎦ ⎥ ⎥ ⎤ ⎣ ⎢ ⎢ ⎡ a b c d ⎦ ⎥ ⎥ ⎤ = ⎣ ⎢ ⎢ ⎡ 5 − 1 3 − 8 3 − 2 6 5 ⎦ ⎥ ⎥ ⎤
Solve the matrix equation above to get the coefficient a , b , c and d . You may find the inverse matrix to solve or use Gaussian elimination method as follows.
⎣ ⎢ ⎢ ⎡ − 6 4 2 7 − 8 1 1 6 9 4 1 − 4 3 − 2 1 1 1 1 1 ∣ ∣ ∣ ∣ − 2 6 5 − 8 3 − 1 3 5 ⎦ ⎥ ⎥ ⎤
⇒ R 1 R 2 − 2 7 R 4 R 1 − 8 R 3 ( 8 R 3 + R 3 ) / 3 → R 1 → R 2 → R 3 → R 4 ⇒ ⎣ ⎢ ⎢ ⎡ − 6 4 0 0 0 1 6 − 1 8 − 1 6 4 − 4 − 2 4 1 2 2 1 − 2 6 − 7 3 ∣ ∣ ∣ ∣ − 2 6 5 − 2 1 8 − 1 6 1 9 ⎦ ⎥ ⎥ ⎤
⇒ R 1 R 2 / 2 R 3 + 4 8 R 4 2 R 2 + 9 R 4 → R 1 → R 2 → R 3 → R 4 ⇒ ⎣ ⎢ ⎢ ⎡ − 6 4 0 0 0 1 6 − 9 0 0 − 4 − 1 2 2 0 − 3 0 1 − 1 3 5 − 2 5 ∣ ∣ ∣ ∣ − 2 6 5 − 1 0 9 − 1 2 5 − 3 5 5 ⎦ ⎥ ⎥ ⎤
⇒ R 1 R 2 R 3 − ( 2 R 4 + 3 R 3 ) / 3 5 → R 1 → R 2 → R 3 → R 4 ⇒ ⎣ ⎢ ⎢ ⎡ − 6 4 0 0 0 1 6 − 9 0 0 − 4 − 1 2 2 0 0 1 − 1 3 5 1 ∣ ∣ ∣ ∣ − 2 6 5 − 1 0 9 − 1 2 5 3 1 ⎦ ⎥ ⎥ ⎤
⇒ R 1 R 2 ( R 3 − 5 R 4 ) / 2 0 R 4 → R 1 → R 2 → R 3 → R 4 ⇒ ⎣ ⎢ ⎢ ⎡ − 6 4 0 0 0 1 6 − 9 0 0 − 4 − 1 2 1 0 1 − 1 3 0 1 ∣ ∣ ∣ ∣ − 2 6 5 − 1 0 9 − 1 4 3 1 ⎦ ⎥ ⎥ ⎤
⇒ R 1 − ( R 2 + 1 2 R 3 + 1 3 R 4 ) / 9 R 3 R 4 → R 1 → R 2 → R 3 → R 4 ⇒ ⎣ ⎢ ⎢ ⎡ − 6 4 0 0 0 1 6 1 0 0 − 4 0 1 0 1 0 0 1 ∣ ∣ ∣ ∣ − 2 6 5 − 1 4 − 1 4 3 1 ⎦ ⎥ ⎥ ⎤
⇒ − ( R 1 − 1 6 R 2 + 4 R 3 − R 4 ) / 6 4 R 2 R 3 R 4 → R 1 → R 2 → R 3 → R 4 ⇒ ⎣ ⎢ ⎢ ⎡ 1 0 0 0 0 1 0 0 0 0 1 0 0 0 0 1 ∣ ∣ ∣ ∣ 2 − 1 4 − 1 4 3 1 ⎦ ⎥ ⎥ ⎤
⇒ a = 2 b = − 1 4 c = − 1 4 d = 3 1
⇒ p ( x ) = x 4 + 2 x 3 − 1 4 x 2 − 1 4 x + 3 1
⇒ p ( 4 ) = 2 5 6 + 2 ( 6 4 ) − 1 4 ( 1 6 ) − 1 4 ( 4 ) + 3 1 = 2 5 6 + 1 2 8 − 2 2 4 − 5 6 + 3 1 = 1 3 5
Therefore, ∣ p ( 4 ) + 4 ∣ = 1 3 5 + 4 = 1 3 9
Very complex... but very nice
Problem Loading...
Note Loading...
Set Loading...
I kinda see that p ( x ) = 7 − x 2 for x = 1 , − 2 , 3 , − 4 . Every time ∣ x ∣ increases by 1 , p ( x ) decreases by 3 , 5 , 7 . That is some sight of quadratic sequence with no terms of x .
Which means p ( x ) − 7 + x 2 = 0 has roots x = 1 , − 2 , 3 , − 4 .
Therefore, p ( x ) − 7 + x 2 = c ( x − 1 ) ( x + 2 ) ( x − 3 ) ( x + 4 ) for some constant c .
And p ( x ) is also monic, that means c = 1 .
p ( x ) = ( x − 1 ) ( x + 2 ) ( x − 3 ) ( x + 4 ) − x 2 + 7
Plug in x = 4 we get p ( 4 ) = 3 × 6 × 1 × 8 − 4 2 + 7 = 1 3 5 ~~~
Just plus 4 to 135 if you say that the answer is not 135. =_="